مدى تحقق معايير الدراسة الدولية (TIMSS,2019) في منهاج سلسلة كامبريدج لمادة الرياضيات للصف الثامن بسلطنة عمان: The extent to which the international study standards (TIMSS, 2019) are achieved in the Cambridge series curriculum for mathematics for the eighth grade in the Sultanate of Oman - Said Salim Al Hudaify, Salim; Bin Nik Abdullah, Nik Md. Saiful Azizi; Said Al Wahaiby, Salim (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
ملخص البحث هدفت الدراسة إلى تقييم مدى تضمّن محتوى كتب سلسلة كامبريدج للرياضيات للصف الثامن الأساسي في سلطنة عمان لمعايير الدراسة الدولية (TIMSS, 2019). استخدمت الدراسة المنهج المختلط لتحليل المحتوى، ووزّعت استبيانات على عينة من معلمي ومشرفي الرياضيات. توصلت النتائج إلى تحقيق محتوى السلسلة نسبة عالية من معايير (TIMSS) في بعض المجالات مثل الأعداد، ولكنها أظهرت فجوات في مجالات أخرى مثل الهندسة. بناءً على النتائج، أوصت الدراسة بإعادة هيكلة محتوى المناهج لتحقيق توازن أفضل وضمان توافقها مع معايير (TIMSS, 2019)، بما يدعم تحسين مستويات التحصيل للطلاب العمانيين في الرياضيات. ABSTRACT This study aimed to evaluate the extent to which the content of the Cambridge Mathematics series for eighth grade in Oman aligns with the standards of the International Study (TIMSS, 2019). A mixed-methods approach was adopted, involving content analysis and questionnaires distributed to sample mathematics teachers and supervisors. The findings revealed a high alignment of the series’ content with TIMSS standards in some areas, such as numbers, while highlighting gaps in other areas, such as geometry. Based on these results, the study recommended restructuring the curriculum to achieve better balance and alignment with TIMSS (2019) standards, thereby enhancing the mathematics achievement levels of Omani students.